Correlational study: Self-esteem and fear of missing out (FoMO) in emerging adulthood - Dwi Isneniah; Reni Nuryani; Sri Wulan Lindasari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Emerging adulthood is a period of self-exploration or identity. In this era, individuals build relationships to connect with other people through social media. Dependence on social media has negative impacts, one of which is anxiety. The anxiety disorder that appears is called fear of missing out (FoMO). Symptoms can be seen from dependence on cell phones, tension when not accessing social media, and obsession with what other individuals upload. The impact is a feeling of inferiority. Low self-satisfaction in an individual's life encourages high levels of FoMO and has negative impacts such as decreased academic achievement, difficulty communicating with other people and disrupting developmental stages in the emerging adulthood phase. Purpose: To determine the relationship between self-esteem and fear of missing out (FoMO) in emerging adulthood. Method: Quantitative descriptive with a correlational approach. The sample in this study amounted to 343 respondents with a sampling technique using proportional stratified random sampling. The research instrument used was a standard self-esteem questionnaire, namely the Rosernberg Self-esteem Scale (RSES) with a validity result of r ≤ 0.30 and a reliability level of 0.889 Cronbach's Alpha, in addition the fear of missing out scale (FoMOS) questionnaire was used with a validity result of r ≤ 0.30 and The reliability level is 0.661 Cronbach's Alpha. Results: The majority of self-esteem levels in emerging adulthood are in the medium category. Obtained p-value <0.001, which means p<α (0.05) indicates a significant relationship between self-esteem and FoMO that occurs in emerging adulthood. Conclusion: There is a significant influence between high self-esteem and low levels of fear of missing out (FoMO) in emerging adulthood. Suggestion: Emerging adulthood who experience high FoMO with low self-esteem can make self-improvement by reducing excessive use of social media to minimize the occurrence of prolonged feelings of low self-esteem. Keyword: Emerging Adulthood; Fear of Missing Out (FoMO); Self-Esteem. Pendahuluan: Manusia dewasa awal merupakan masa eksplorasi jati diri atau identitas. Pada masa ini, individu membangun relasi untuk terhubung dengan orang lain melalui media sosial. Ketergantungan terhadap media sosial memberikan dampak negatif, salah satunya adalah kecemasan. Gangguan kecemasan yang muncul disebut fear of missing out (FoMO). Gejalanya dapat terlihat dari ketergantungan akan ponsel, ketegangan saat tidak mengakses media sosial, dan obsesi dengan apa yang diunggah oleh individu lain. Dampak yang ditimbulkan adalah perasaan rendah diri. Rendahnya kepuasan diri dalam hidup individu mendorong tingkat FoMO yang tinggi dan memberikan dampak negatif seperti, prestasi akademik menurun, kesulitan untuk berkomunikasi dengan orang lain dan mengganggu tahap perkembangan pada fase dewasa awal. Tujuan: Untuk mengetahui hubungan harga diri dengan fear of missing out (FoMO) pada emerging adulthood. Metode: Deskriptif kuantitatif dengan pendekatan korelasional. Sampel dalam penelitian ini berjumlah 343 responden dengan teknik pengambilan sampel menggunakan proportionate stratified random sampling. Instrumen penelitian yang digunakan berupa kuesioner baku harga diri yaitu Rosenberg Self-esteem Scale (RSES) dengan hasil validitas r ≤ 0.30 dan tingkat reabilitas 0.889 Alpha Cronbach’s, selain itu digunakan kuesioner fear of missing out scale (FoMOS) dengan hasil validitas r ≤ 0.30 dan tingkat reabilitas 0.661 Alpha Cronbach’s. Hasil: Tingkat harga diri pada emerging adulthood mayoritas berada pada kategori sedang. Didapatkan p-value <0.001 yang artinya p<α (0.05) menunjukkan adanya hubungan yang signifikan antara harga diri dengan FoMO yang terjadi pada emerging adulthood. Simpulan: Terdapat pengaruh yang signifikan antara tingginya nilai harga diri menjadikan rendahnya tingkat fear of missing out (FoMO) pada emerging adulthood. Saran: Emerging adulthood yang mengalami FoMO tinggi dengan harga diri rendah dapat melakukan perbaikan diri dengan mengurangi penggunaan media sosial yang berlebihan guna meminimalisir terjadinya perasaan rendah diri yang berkepanjangan. Kata Kunci: Dewasa Awal; Fear of Missing Out (FoMO); Harga Diri.